1997
DOI: 10.1046/j.1468-2982.1997.1702119.x
|View full text |Cite
|
Sign up to set email alerts
|

Classical Homeopathic Treatment of Chronic Headaches

Abstract: We conducted a randomized, placebo‐cor rolled, double‐blind clinical trial in order to determine the efficacy of classical homeopathic therapy in patients with chronic headaches. After 6 weeks of baseline observation, patients received either the prescribed individualized homeopathic medication or an indistinguishable placebo for 12 weeks. Outcome parameters were headache frequency, duration, and intensity, measured daily by diary. Use of medication for acure headache was also monitored. Of the 98 patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
10

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 2 publications
1
67
0
10
Order By: Relevance
“…In contrast, the only randomised Witt/Lüdtke/Willich controlled trial [11] that included non-migraine headaches (98 patients, any type of chronic headache except post-traumatic, treated for 12 weeks) saw no difference from placebo. Its patients were older than our patients (median verum group = 51 years, median placebo group = 46 years; our study: median = 37.5 years) and had suffered from migraine and/or headache for much longer (mean = 29 years, median = 23 years; our study: median = 14.5 years).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, the only randomised Witt/Lüdtke/Willich controlled trial [11] that included non-migraine headaches (98 patients, any type of chronic headache except post-traumatic, treated for 12 weeks) saw no difference from placebo. Its patients were older than our patients (median verum group = 51 years, median placebo group = 46 years; our study: median = 37.5 years) and had suffered from migraine and/or headache for much longer (mean = 29 years, median = 23 years; our study: median = 14.5 years).…”
Section: Discussionmentioning
confidence: 94%
“…To date, only studies on migraine or studies including any type of cephalalgia have been reported [10][11][12][13][14], only the earliest work [10] (60 patients, chronic migraine, last assessment after 4 months) found superiority in the verum group (in frequency, intensity, duration, spontaneous resolution). Neither Walach [11,12] (98 patients, any type of chronic headache except post-traumatic, treatment duration 12 weeks) nor Whitmarsh [13] (64 patients, migraine, treatment duration 3 months) nor Straumsheim [14] (64 patients, migraine, treatment duration 4 months) found any significant effect beyond placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Die bisher durchgeführten prospektiven Placebo-kontrollierten Studien ergaben keinen Hinweis auf eine Wirksamkeit der Homöopathie (Walach et al 1997, Whitmarsh et al 1997, Ernst 1999, Straumscheim et al 2000.…”
Section: Hömöopathieunclassified
“…Many good quality studies of the last 12 years have yielded negative results, for instance, concerning systematic reviews and meta-analyses [3][4][5][6][7][8][9][10][11] ; infections of the upper respiratory tract and allergic rhinitis 12,13 ; post-operative ileus 14 ; asthma 15 ; warts [16][17][18] ; pain relief and muscle soreness [19][20][21][22][23] ; treatment of adenoid vegetation 24 ; chronic headache [25][26][27][28] ; ear inflammation 29,30 ; eczema 31 ; arthritis 32,33 ; bruising 34,35 ; anxiety 36 ; "provings" (see below) with belladonna, arnica, Pulsatilla and mercury [37][38][39][40][41] and "aggravations" ("good" worsening of symptoms, said by homeopaths to precede patient recovery) 42 . Detailed comments on many of these studies are published 2,5,43 .…”
Section: Clinical Trialsmentioning
confidence: 99%